Application of Scratch Testing for the Assessment of the Adherent Properties of Scales and CO2 Corrosion Product Layers and their Relation to Corrosion. (September 2021) - Prieto, Claudia; Mansoori, Hamed; Brown, Bruce; Singer, Marc; Young, David
Graphical abstract: Highlights: Substitutional Ca 2+ in Fex Cay CO3 was not detrimental to steel protectiveness. Corrosion protection was conferred by FeCO3 that grew underneath the initial CaCO3 layer. Shear stresses in pipelines are insufficient to significantly damage Fex Cay CO3 layers. Shear stresses associated with removal of Fex Cay CO3 are unrelated to fracture toughness. Abstract: Protective corrosion product layers, such as iron carbonate, can govern pipeline corrosion; their formation being associated with operational conditions (high [Fe 2+ ], pH > 6.0, T > 70 °C). Brines contain Ca 2+ that can incorporate as a substitutional cation in the iron carbonate lattice, potentially compromising the mechanical integrity of the protective layer. This work utilized scratch testing as an analytical technique that provides more information on layer adherence than indentation methods. It was demonstrated that the presence of iron calcium carbonate layers contributes to the formation of a protective and mechanically stable iron carbonate layer adjacent to the steel surface.